The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1037/0022-006x.68.5.843
|View full text |Cite
|
Sign up to set email alerts
|

An experimental evaluation of theory-based mother and mother–child programs for children of divorce.

Abstract: This study evaluated the efficacy of 2 theory-based preventive interventions for divorced families: a program for mothers and a dual component mother-child program. The mother program targeted mother-child relationship quality, discipline, interparental conflict, and the father-child relationship. The child program targeted active coping, avoidant coping, appraisals of divorce stressors, and motherchild relationship quality. Families with a 9-to 12-year-old child (N = 240) were randomly assigned to the mother,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
314
0
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 200 publications
(335 citation statements)
references
References 56 publications
18
314
0
3
Order By: Relevance
“…We conducted analyses of mediation for each significant main effect and Program ϫ Baseline Status interaction effect of the MP as contrasted with the LC on mental health problem outcome variables (Wolchik et al, 2000) using SEM with maximum likelihood estimation. 7…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We conducted analyses of mediation for each significant main effect and Program ϫ Baseline Status interaction effect of the MP as contrasted with the LC on mental health problem outcome variables (Wolchik et al, 2000) using SEM with maximum likelihood estimation. 7…”
Section: Resultsmentioning
confidence: 99%
“…The NBP (Wolchik et al, 2000) was designed to change potentially modifiable correlates that, demonstrated by research, were associated with mental health problems for children of divorce. The small theory (Lipsey, 1990) of the intervention is that program-induced change in these variables would lead to (i.e., mediate) program-induced change in children's mental health problems.…”
Section: Nbp: a Theoretically Based Preventive Interventionmentioning
confidence: 99%
See 3 more Smart Citations